Modern engineering mathematics - JJames, Glyn (Pearson, 2020)
"Modern Engineering Mathematics, 6th Edition by Professors Glyn James and Phil Dyke, draws on the teaching experience and knowledge of three co-authors, Matthew Craven, John Searl and Yinghui Wei, to provide a comprehensive course textbook explaining the mathematics required for studying first-year engineering. No matter which field of engineering you will go on to study, this text provides a grounding of core mathematical concepts illustrated with a range of engineering applications. Its other hallmark features include its clear explanations and writing style, and the inclusion of hundreds of fully worked examples and exercises which demonstrate the methods and uses of mathematics in the real world. Woven into the text throughout, the authors put concepts into an engineering context, showing you the relevance of mathematical techniques and helping you to gain a fuller appreciation of how to apply them in your studies and future career. A leader in its field, Modern Engineering Mathematics offers: Clear explanations of the mathematics required for first-year engineering. An engineering applications section in every chapter that provides arresting ways to tackle and model problems, showing how mathematical work is carried out in the real world. 500 fully worked examples, including additional examples for this 6th Edition, reinforce the role of mathematics in the various branches of engineering. Over 1200 exercises to help you understand how concepts work and encourage learning by doing. Integration of MATLAB environment as well as MAPLE software, showing how these can be used to support your work in mathematics. New inclusion of R software within 'Data Handling and Probability Theory' chapter. Free online 'refresher units' covering maths topics that you may not have used for some time. These can be found on a companion website linked from www.pearsoned.co.uk/james"--